Features of Galicia Sports Press Functioning in 1920s — 1930s - Yu. A. Sazonova; T. I. Yaroshovets (Научный диалог, 2021)
The results of the typological analysis of the Galician sports press of the 1920s—1930s are presented. The quantitative growth of sports publications in Galicia during the analyzed period is noted, despite the fact that the region is under Polish hegemony, and the role of the regional sports press as a catalyst of national consciousness is emphasized. The sociopolitical conditions for the development of sports periodicals and general trends in the program policy of Galician sports publications have been determined. The novelty of the research is seen in the identification of the characteristic regional dominants of the sports periodicals in Galicia through the implementation of content analysis of Galician publications and a comparative analysis of sports journalism in Galicia and the Ukrainian SSR of the 1920s—1930s. The author’s development of the periodization of the sports press of Galicia of the indicated era based on the unification of sociopolitical, typological, problem-thematic, genre features of publications in a certain chronological period is presented, constitutional dominants of each period are indicated. Particular attention is paid to the review and content analysis of the most representative media of each period of the sports press of Galicia in the 1920s and 1930s, where the units of scientific observation were the goals and objectives of the publications, the composition of the editorial boards, the genre and problem-thematic ranges of materials. An overview analysis of the conditions of development, the characteristics of content, structure, genre-thematic palette, authorship of the sports media of Galicia in the context of sports journalism of Ukraine in the first half of the twentieth century is presented in conclusion.